Factors associated with poor outcome in maxillofacial fractures - Phanzu Reagan; Ntima Albert; Sokolo Richard; Kadinekene Joseph; Kubiluka Joseph; Dilu Frederick; Madaka Claude; Mbombo Wilfrid; Ntsambi Glennie (Balkan Journal of Dental Medicine)
Background/Aim: Patients with maxillofacial fractures can progress to complications and death. This study investigated the factors associated with poor outcome in these patients at the Cliniques Universitaires de Kinshasa/ University of Kinshasa. Material and Methods: This was a cross-sectional study conducted from 01/01/2018 to 31/12/ 2023. It involved maxillofacial fracture patients admitted to the emergency department, intensive care unit and maxillofacial surgery. Socio-demographic, clinical, paraclinical and evolutionary data were collected and analysed with Statistical Package for Social Sciences (SPSS) 25.0 software using Student's t-test, Pearson's Chi-square test or Fischer's exact test and logistic regression with a p-value <0.05. Results: Sixty patients were enrolled. Males predominated (sex ratio M/F: 5). The mean age was 32.13 ± 15.7 years. Road traffic accidents (86.7%) were the leading cause of facial fractures, often involving motorcyclists (33.3%). Latero-basi-cranial fractures and cerebral contusions were the most common associated injuries. Their association was significant (p=0.028). The outcome was favourable in 68.3% of cases. Complications included soft tissue infection (18.3%) and osteitis in 3.3% of cases. Death occurred in 10.0% of cases. The presence of associated brain lesions was incriminated as a major factor correlated with poor outcome (p=0.026, ORa = 9.24, CI 95%=1.30-65.48). Conclusions: This study showed that maxillofacial fractures are common. They affect young males involved in motorbike accidents, with a higher rate of complications than in the literature. The presence of cerebral lesions was the only factor associated with poor outcome. A prospective multicentre study would be useful to confirm these results.